Análise temporal da cobertura do solo na zona de amortecimento de reserva biológica - Fengler, Felipe Hashimoto; Silva, Alexandre Marco da [UNESP]; Peche Filho, Afonso; Storino, Moises; Ribeiro, Admilson Írio [UNESP]; Medeiros, Gerson Araújo de [UNESP] (My University, 2012)
The Municipal Biological Reserve of Serra do Japi shelters an important forest remnant of Atlantic Rainforest in the state of São Paulo. For its ecological importance, were created instruments for environmental and territorial management of the Conservation Unit, with the regulation of the use and occupation of the land in its Buffer Zone (BZ) in 2004. The objective of this study was to analyze the evolution of the land cover in the BZ region of the Municipal Biological Reserve of Serra do Japi in Jundiaí-SP, between 1989 and 2010. It was used in this study the image analysis of the satellite LANDSAT-TM5, with the help of software ILWIS and IDRISI. The results showed that urban occupation has increased 37.47% and the agro pastoral and reforestation areas have decreased 36.62% and 72.22% respectively, while forest areas have increased 49.57%. However, the relative importance of the forest area in BZ ranged from 46.60% in 1989 to 69.71% in 2010, leading to the conclusion that this region was favored by changes in land cover in the period evaluated, despite strong pressure for urban expansion in its surroundings.

A Reserva Biológica Municipal da Serra do Japi abriga um importante remanescente florestal da Mata Atlântica, no interior do estado de São Paulo. Pela sua importância ecológica, foram criados instrumentos para a gestão ambiental e territorial da Unidade de Conservação, com a regulamentação do uso e ocupação do solo na sua Zona de Amortecimento (ZA), em 2004. O objetivo do presente trabalho foi analisar a evolução da cobertura das terras na região da ZA da Reserva Biológica Municipal da Serra do Japi, em Jundiaí-SP, entre 1989 e 2010. Empregou-se nesse estudo a análise de imagens do satélite LANDSAT-TM5, com o auxilio dos softwares IDRISI e ILWIS. Os resultados mostraram que a ocupação urbana aumentou 37,47% e as áreas agropastoris e de reflorestamento diminuíram 36,62% e 72,22% respectivamente; enquanto as áreas de mata aumentaram 49,57%. Todavia, a importância relativa da área de mata na ZA variou de 46,60%, em 1989, a 69,71%, em 2010, levando-se a conclusão de que essa região foi favorecida pelas mudanças na cobertura do solo, no período avaliado, apesar da forte pressão pela expansão urbana no seu entorno.
Temporal analysis of soil cover in the buffer zone of biological reserve
Keywords: Remote sensing; Environmental management; Conservation unit; Sensoriamento remoto; Gestão ambiental; |Unidade de conservação